Differential Effects of HOXB4 and NUP98-HOXA10hd on Hematopoietic Repopulating Cells in a Nonhuman Primate Model - Watts, Korashon L. (Mary Ann Liebert, Inc., 2011)
Expansion of hematopoietic stem cells (HSCs) is beneficial in settings where HSC numbers are limited, such as cord blood transplantation. The human homeobox transcription factor HOXB4 has been shown to enhance stem cell expansion in several experimental models. We have shown previously that HOXB4 overexpression in monkey CD34(+) cells has a dramatic effect on expansion and engraftment of short-term repopulating cells. Here, we wished to compare the effects of HOXB4 and another candidate gene, NUP98-HOXA10hd (NA10hd). We used a competitive repopulation assay in pigtailed macaques to study engraftment of CD34(+) cells modified with gammaretroviral HOXB4YFP or NA10hdGFP. We found that HOXB4YFP contributed more to early hematopoiesis (<30 days), whereas NA10hdGFP contributed more to later hematopoiesis. In each case, we observed two distinct peaks in engraftment of NA10hd-transduced cells, one within 20 days post transplant and another after 5–6 months. Analysis of CD14(+), CD3(+), and CD20(+) subsets confirmed that higher percentages of cells of each lineage were derived from NA10hdGFP(+) progenitors than from HOXB4YFP(+) progenitors. In conclusion, we show that HOXB4 and NA10hd both have a significant impact on hematopoietic reconstitution; however, these effects are differential and therefore may offer complementary strategies for HSC expansion.